Analysis of Factors That Influence the Quality of Company Financial Reports - Handayani, Ida Ayu Ria Paramita; Junitasari, Putu Diah Krisna; Irmayani, Ni Wayan Dian (International Journal of Business, Law, and Education, 2024)
This research aims to examine the influence of company scale, ownership composition, and level of market concentration on the quality of financial reports of manufacturing companies listed on the Indonesia Stock Exchange (BEI). The data used comes from the annual financial reports of 120 companies during the 2015-2017 period. The purposive sampling method was used for sample selection. The results of data analysis show that there is a significant correlation between independent variables and the quality of financial reports. The results of the regression test show that company scale, ownership composition, and level of market concentration significantly influence the quality of financial reports. These findings indicate that companies with large size, consolidative ownership structures, and market dominance tend to produce higher quality financial reports. The implications of this research highlight the importance of good information management in a business context, as well as the need for transparency and accountability in corporate financial reporting.